Legal mechanism on citizen protection through constitutions of vietnam - Phan, Thanh Ha (Đại học Quốc gia Hà Nội, 2020)
The paper analyses the concept, characteristics, and constituent elements of the legal mechanism for citizen protection, and at the same time, reviews the recognition process of citizen protection mechanism in Vietnam through the Constitutions (from the Constitution of 1946 until now) and achievements in the 2013 Constitution. Analysis and research of Constitutions have shown the ideology and practice of citizen protection in Vietnam, established through regulations on citizen protection to a certain extent, including basically property rights (legitimate income, savings, house, living materials, production materials) and inheritance right (of individuals, group of individuals, legal persons), family and marriage regime; rights to health, life, honour, dignity of citizens… Some raised problems are related to the specific limitations in the provisions of the Constitution on Legal Mechanism on Citizen Protection in Vietnam such as: (i) The regulations on citizen protection in Vietnam have not been clarified and agreed upon; (ii) The legal mechanism for citizen protection in the Constitution is incomplete and unsystematic; (iii) There are no specific procedures and sanctions for the determination of legal responsibility (besides political responsibility) in the State in the legal mechanism for citizen protection in Vietnam